2020
DOI: 10.1098/rsos.191648
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic influence of 16- s -16 gemini surfactants on the rate constant of histidine and ninhydrin

Abstract: The present paper reports the catalytic influence of 16-s-16 (spacer (s) = 4, 5, 6) gemini surfactants on the rate constant of histidine and ninhydrin at 343 K and pH 5.0 using the spectrophotometric technique. The effect of varying amounts of geminis was made on the rate constant of histidine and ninhydrin keeping other constituents constant. Characteristics of the rate constant (k ψ ) versus [gemini] depict the effect of surfactants on the rate constant. A systematic explanation about the effect of surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The study deals with the synthesis and characterization of gemini surfactants and their influence on the kinetic behavior of ninhydrin with zinc-glycylleucine. The reason for choosing this particular study is the mechanism of ninhydrin with amino acids reaction in water, conventional surfactants (CTAB, cetylpyridinium bromide, CPB) and the various solvent medium is well recognized [24][25][26][27][28][29][30]59 . Under the identical reaction condition, it was found that the study was catalyzed and accelerated quite enough in gemini surfactants (below their cmc value) than aqueous medium 73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study deals with the synthesis and characterization of gemini surfactants and their influence on the kinetic behavior of ninhydrin with zinc-glycylleucine. The reason for choosing this particular study is the mechanism of ninhydrin with amino acids reaction in water, conventional surfactants (CTAB, cetylpyridinium bromide, CPB) and the various solvent medium is well recognized [24][25][26][27][28][29][30]59 . Under the identical reaction condition, it was found that the study was catalyzed and accelerated quite enough in gemini surfactants (below their cmc value) than aqueous medium 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Ninhydrin reactions are one of the most fundamental and biochemical studies. Ninhydrin, a chemical reagent, is used enormously for detection of amine functional group wherein it reacts with an amino group and generates diketohydrindylidene-diketohydridamine (DYDA) [22][23][24][25][26][27][28][29][30] . The color of the product formed between the reaction of ninhydrin and amino acids disappears at room temperature, several efforts were performed towards the stability of products that include the formation of the metal complex with amino acids, change of solvent, presence of conventional monomeric surfactant 28,[31][32][33] .…”
mentioning
confidence: 99%
“…Gemini surfactants can produce aggregates such as micelles, bilayers, vesicles, and other structures with different additives [88]. Several authors have carried out recent studies related to the formation of aggregates from gemini surfactants due to the benefits of these surfactants compared to those with a single hydrophobic chain.…”
Section: Micelles Formationmentioning
confidence: 99%
“…The rate constant (k ψ ) values were estimated as an average of at least triplicate runs. A detailed procedure in regard of kinetic measurements is available in the literature published previously [57][58][59][60][61][62][63].…”
Section: Kinetic Measurementsmentioning
confidence: 99%